Permen Ceting (Persiapan Menyusui Cegah Stunting pada Ibu Hamil) di Desa Sungai Tabuk Kota Rt 6 - Silfia Silfia; Nurul Hidayah; Elysa Marini; Lisda Handayani (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Stunting is caused by many factors, of which the most decisive intervention is that carried out during the first 1000 days of life. One of the problems that causes stunting is a lack of nutritional intake during pregnancy, resulting in fetal growth failure which is the beginning of stunting. Based on the results of the data review, the lack of exclusive breastfeeding has been found. However, the priority problems that can be drawn from this problem are regarding the preparation and provision of exclusive breastfeeding aimed at pregnant women and women of childbearing age. The purpose of the activity is to increase information and knowledge of pregnant women and women of childbearing age regarding the importance of preparing for exclusive breastfeeding. The location of the implementation is in Sungai Tabuk Kota Village RT 06, Sungai Tabuk District, Banjar Regency. The target of exclusive breastfeeding preparation to prevent stunting counseling, includes various groups ranging from pregnant women to women of childbearing age. The results obtained from this service are increased knowledge and awareness of mothers regarding the importance of providing exclusive breastfeeding to prevent stunting